Implementation of a Broad Range Smart Temperature Measurement System using Auto-Selected Multi-Sensor Core in LabVIEW Environment - Ghaly, S. M. A.; Khan, M. O.; El Mehdi, S. O.; Al-Awad, M.; Asad Ali Μ.; Al-Snaie, K. A. (Engineering, Technology & Applied Science Research, 2019)
A conventional temperature sensing system employs a single transducer to convert temperature into an electrical signal. Such a system suffers from the limitation of the sensing range of the sensing device thereby affecting its accuracy and its capability. Therefore to make an accurate measurement in a typically abrupt temperature varying environment, a broad range high precision sensor is required. In this paper, an attempt is made to implement a wide spectrum temperature measurement system using auto-selected multi-sensor core in LabVIEW. This multi-sensor core can be composed of a set of different sensors having different capabilities to measure different temperatures ranges. These sensors are auto-selected by the program depending on the environment. This concept may be useful for space applications or it can also be useful for the monitoring of temperature and pressure in an oil/gas transportation or supply by means of underground/sea pipeline system or in a refinery plant. Further, this may also be applied for high precision temperature sensing in magnetic resonance imaging system applications.